2016
DOI: 10.1007/s12639-016-0872-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of deltamethrin and chlorpyriphos in bovine ticks in and around Jabalpur

Abstract: Efficacy of chlorpyriphos (Classic*20, 20% EC) and deltamethrin (Butox, 1.25% EC) was assessed by spraying these drugs on cattle and buffaloes which were naturally infested with ticks at the concentration of 2.5 and 2 ml/l, respectively. Results of the study demonstrated the prolonged effect of chlorpyriphos when compared with deltamethrin. Moreover, residual effect of chlorpyriphos remained even after 14 days of treatment with 28.57% animals showing reinfestation, while in deltamethrin treated animals; the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…This is consistent with the findings of Klafke et al (2021), who found that chlorpyrifos (1 mL/L) caused 100% mortality to R. microplus . In addition, Katuri et al (2017) found that animals treated by chlorpyrifos (2.5 mL/L) had prolonged protection against re‐infestation by ticks in India.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings of Klafke et al (2021), who found that chlorpyrifos (1 mL/L) caused 100% mortality to R. microplus . In addition, Katuri et al (2017) found that animals treated by chlorpyrifos (2.5 mL/L) had prolonged protection against re‐infestation by ticks in India.…”
Section: Discussionmentioning
confidence: 99%
“…microplus. Gaur et al, (2016) and Katuri et al, (2017) reported resistance against deltamethrin, cypermethrin, and diazinon. It is concluded from present work that deltamethrin at 75 and 100 ppm can be recommended for tick control/irradication programme.…”
Section: Results a N D Discussionmentioning
confidence: 99%
“…Reports of deltamethrin resistance in R. microplus ticks are also available from various parts of North India ( 7 , 17 , 24 – 27 ). In a study at Central India (Jabalpur, Madhya Pradesh), deltamethrin treated animals showed re-infestation with ticks by the 14 th day of treatment, which provides indication of the reduced efficacy of deltamethrin in tick control in animals and animal sheds ( 23 ). Later, high resistance ratio (RF= 22.35 to 34.64) of field tick against deltamethrin was also recorded from Mhow districts in Madhya Pradesh ( 28 ).…”
Section: Discussionmentioning
confidence: 99%